Extracting body function information using rule-based methods: Highlighting structure and formatting challenges in clinical text - Divita, Guy; Coale, Kathleen; Maldonado, Jonathan Camacho; Silva, Rafael Jiménez; Rasch, Elizabeth (Frontiers in Digital Health, 2022)
This paper describes the identification of Body Function (BF) mentions within clinical text within a large, national, heterogeneous corpus to highlight structural challenges presented by clinical text. Body Function in clinical documents provides information on dysfunction or impairments in the function or structure of organ systems or organs. BF mentions are embedded in highly formatted structures where the formats include implied scoping boundaries that confound existing Natural Language Processing (NLP) segmentation and document decomposition techniques. This paper describes follow-up work to adapt a rule-based system created using NIH records to a larger, more challenging corpus of SSA data. Results of these systems provide a baseline for future work to improve document decomposition techniques.